1984
DOI: 10.1128/mcb.4.7.1213
|View full text |Cite
|
Sign up to set email alerts
|

Structurally and functionally modified forms of pp60v-src in Rous sarcoma virus-transformed cell lysates.

Abstract: When analyzed from transformed cell lysates, pp60v-src, the product of the Rous sarcoma virus src gene, typically appears as a single polypeptide of 60,000 molecular weight, phosphorylated at two major sites, an amino-terminal region serine residue and carboxy-terminal region tyrosine residue. We describe here the identification of variant forms of pp6-vsrc present in transformed cell lysates that exhibited an altered electrophoretic mobility in sodium dodecyl sulfate-polyacrylamide gels. This change in migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 31 publications
8
75
0
Order By: Relevance
“…5 lanes 1 and 2), 10 (lanes 3 and 4), or 100 (lanes 5 and 6) FiM ATP were immunoprecipitated and resolved by gel electrophoresis. The bands corresponding to pp6f-vsrc were excised, reelectrophoresed in the presence of 5 (lanes 1, 3, and 5) or 50 (lanes 2, 4, and 6) ng of S. aureus V8 protease, and analyzed by autoradiography. The positions of unproteolyzed pp60v-src and the V8 proteolytic products corresponding to the amino-terminal 34,000-dalton (N34) and carboxy-terminal 26,000-dalton (C26) fragments are denoted in the margin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 lanes 1 and 2), 10 (lanes 3 and 4), or 100 (lanes 5 and 6) FiM ATP were immunoprecipitated and resolved by gel electrophoresis. The bands corresponding to pp6f-vsrc were excised, reelectrophoresed in the presence of 5 (lanes 1, 3, and 5) or 50 (lanes 2, 4, and 6) ng of S. aureus V8 protease, and analyzed by autoradiography. The positions of unproteolyzed pp60v-src and the V8 proteolytic products corresponding to the amino-terminal 34,000-dalton (N34) and carboxy-terminal 26,000-dalton (C26) fragments are denoted in the margin.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we describe kinetic studies of phosphorylation of amino-and carboxy-terminal sites in membrane-bound pp6Ov-src and suggest that both kinetic parameters and the presence of phosphoprotein phosphatases may limit the extent of amino-terminal phosphorylation. While this work was in progress, Collett et al (5) and Brown and Gordon (1) reported the identification of variant forms of pp6ov-src containing amino-terminal phosphotyrosine in transformed cell lysates. Our work with membrane vesicles complements and extends these findings.…”
mentioning
confidence: 99%
“…4), indicating that not all the pp60csrc molecules in this band were phosphorylated at these additional sites. Second, although phosphorylation of Ser-12 (32) or of unidentified NH2-terminal tyrosines (10,13,72) can cause small decreases in the mobility of fibroblast pp60csrc, there is no known in vivo phosphorylation event which results in such a dramatic shift in the mobility of pp60c-src. Third, the 61-kDa protein does not appear to be VOL.…”
Section: Discussionmentioning
confidence: 99%
“…While the IgG kinase assay is capable of displaying a 10-fold enhancement of pp60csrc kinase activity in the presence of cooperating factors (D. Shalloway et al, manuscript submitted), it does not accurately display kinase activity differences associated with labile pp60v`src tyrosine phosphorylation (9,41). While the monoclonal antibody exogenous substrate kinase assay measures activitation of pp60csrc kinase activity by polyoma middle T (4), it is possible that antibody binding or the presence of contaminating factors perturbs the results.…”
Section: Discussionmentioning
confidence: 99%